Cardiac transesophageal stimulator. - Polo, S.; Sedillo, A.; Colin, L.; Pastelin, G.; Rodriguez Infante, O.; Flores, P. (Revista Mexicana de Ingenieria Biomedica, 1991)
We present a transesophageal stimulator prototype that allows the diagnosis and treatment of arrhythmias taking advantage of the proximity between the posterior wall of the heart and the esophagus.